Association of oxytocin level and less severe forms of childhood maltreatment history among healthy Japanese adults involved with child care - Mizuki, Rie; Fujiwara, Takeo (Frontiers in Behavioral Neuroscience, 2015)
Background: Oxytocin (OT) is known to play a role in stress regulation. The association between childhood maltreatment history and neuropeptide OT concentration is inconsistent due to the varying degrees of severity of childhood maltreatment, among other contributing factors. Less severe forms of childhood maltreatment history might enhance OT concentrations as a response to coping with social stress within the family. The purpose of this study is to investigate the association between less severe forms of childhood maltreatment history and OT concentrations among healthy adults. Method: Eighty-one adults (50 women and 31 men) with 18- to 48-month-old children were recruited using a snowball sample in Tokyo, Japan. Urine samples were collected for OT measurement. Less severe (low and moderate) childhood maltreatment history, including physical abuse, physical neglect, emotional abuse, emotional neglect, and sexual abuse, was assessed using the self-report questionnaire, the Childhood Trauma Questionnaire. Results: Less severe physical abuse was significantly associated with higher OT concentration after adjusting for age (p=0.014). Also, less severe forms of physical abuse were independently significantly associated with higher OT concentration after controlling for other types of childhood maltreatment (p=0.027). A positive dose-response association between the number of less severe childhood maltreatment types and OT concentration was observed (p=0.031). Conclusion: A history of less severe forms of childhood physical abuse was associated with higher OT concentration in healthy adults. Poly-victimization of several types of less severe childhood maltreatment was also associated with higher OT concentrations. Less severe forms of childhood maltreatment might enhance OT concentrations in order to cope with social stress.